2016
DOI: 10.1093/pm/pnw014
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Cosyntropin Versus Epidural Blood Patch for Treatment of Postdural Puncture Headache

Abstract: It is reasonable to consider IV cosyntropin as the treatment of choice for patients in whom EBP is contraindicated or in austere environments where there is limited or no access to anesthesia trained providers. Future research should compare efficacy and cost of prophylaxis to treatment of PDPH with intravenous cosyntropin and evaluate the most effective dosing regimen, including duration, number, and strength of doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Despite the positive results of the aforementioned studies, a systematic review failed to demonstrate any prophylactic effects of epidural saline on PDPH incidence or the need for a blood patch (10). We propose that the triple prophylaxis potentiates the positive effects of individual methods by combining the analgesic effect of morphine, the pressure-equalizing effect of saline, and the increased production of cerebrospinal fluid and endorphin release induced by cosyntropin [16][17]. We may argue that even the small effect of epidural saline is maximized by the addition of the other two strategies.…”
Section: Discussionmentioning
confidence: 87%
“…Despite the positive results of the aforementioned studies, a systematic review failed to demonstrate any prophylactic effects of epidural saline on PDPH incidence or the need for a blood patch (10). We propose that the triple prophylaxis potentiates the positive effects of individual methods by combining the analgesic effect of morphine, the pressure-equalizing effect of saline, and the increased production of cerebrospinal fluid and endorphin release induced by cosyntropin [16][17]. We may argue that even the small effect of epidural saline is maximized by the addition of the other two strategies.…”
Section: Discussionmentioning
confidence: 87%
“…The trial reported by Hakim found that administration of tetracosactide after accidental dural puncture in 90 parturients was associated with a significant reduction in the incidence of PDPH and requirement for epidural blood patch [39]. The efficacy of tetracosactide for the treatment of PDPH in 32 patients has been reported to be 56% (95% CI [33; 79%]) [40], and to be similar to that of epidural blood patch in a study that included 28 patients [41], although 4 of the 15 in the tetracosactide group also received a blood patch. However, a randomized trial that included 18 patients did not find any efficacy of tetracosactide in the treatment of PDPH, nor in the reduction of blood patch use [45].…”
Section: Introductionmentioning
confidence: 98%
“…Alternative treatments have recently been studied; they aim to be less invasive or to reduce headache intensity whilst waiting for the blood patch or the disappearance of PDPH. Several lines of evidence have suggested the effectiveness of adrenocorticotropic hormone (ACTH) in the management of PDPH [33][34][35][36][37][38][39][40][41]. Several mechanisms have been proposed to explain the effects of ACTH or its analogues on headaches.…”
Section: Introductionmentioning
confidence: 99%
“…Now there are several modalities treatment available for the treatment of post dural puncture puncture headache. Of these the most notable one is epidural blood patch [3] , which is considered to be gold standard for PDPH. But it effects are less than 100%.…”
Section: Introductionmentioning
confidence: 99%